The Wright brothers : inventors whose ideas really took flight - Venezia, Mike (New York : Children's Press, 2010)
An introduction to the lives and careers of brothers Wilbur and Orville Wright, who built and flew the first successful powered airplane.
Includes index.
008-012
Keywords: Wright, Wilbur, -- 1867-1912 -- Juvenile literature; Wright, Orville, -- 1871-1948 -- Juvenile literature; Wright, Wilbur, -- 1867-1912; Wright, Orville, -- 1871-1948; Wright, Wilbur, -- 1867-1912; Wright, Orville, -- 1871-1948; Aeronautics -- United States -- Biography -- Juvenile literature; Aeronautics -- United States -- History -- Juvenile literature; Aeronautics; Aeronautics -- United States -- History; Aeronautics -- Biography; Aeronautics -- United States -- History